Appropriate school starting age: A focus on the cognitive and social development of a child - Mahwish Ali Baber (Journal of Education and Educational Development, 2020)
The early years are the most important in the emotional, social,physical and cognitive development of a child.. A child’s earlyexperiences have an immense impact on the development of his/her physical, emotional and cognitive skills. Therefore, it is veryimportant to understand the kind of environment children need inthe early years for their healthy development and also to understandwhen it is appropriate to begin their schooling in order to optimizetheir social, cognitive and emotional well-being. It is observed thatthe number of formal pre-schools have increased drastically in thepast few years. Children between the ages of one to five are attendingthese pre-schools. This paper attempts to look into the variousresearches conducted to find out how early childhood experiencesaffect children; how their emotional and cognitive developmentoccurs; and most importantly, whether or not starting school at anage earlier than seven years, benefits their academic achievementin the long run. The findings of the various researches indicate thatchildren in the early years need to spend time in free play rather thanin structured and scheduled school environments. This will also helpthem in their future academic success. Thus, starting school earlierthan seven years of age is not beneficial socially or academically inthe long run.
Keywords: Academic performance; cognitive development theory; early childhood education